Strategy For The Implementation of Cleaner Production to Intensive Meatduck Farming in Tuban District - Kholiq, Imron; Hakim , Abdul; Laksono, Amin Setyo (Graduate School, Universitas Brawijaya, 2024)
Duck farming is a business that has been carried out for generations by the community. Even, duck farming is determined as an alternative effort to provide employment to reduce poverty in Tuban district. On the other hand intensive duck farming has potential that causes environmental problems. The purpose of this study is to evaluate and develop a strategy for implementing cleaner production to intensive a duck farming in Tuban district. The results of the trend in applying the principle of re-think, re-use and re-cycle among famers of an intensive duck farming in Tuban District show all farmers have applied three from five principles (5-R). The trend of applying the principle of recovery is still in the development stage, not all farmers apply the principle of re-deduction. While the trend of applying the re-covery principle is still very low (no farmer applies re-covery principles). The option of applying cleaner production is to ferment duck feed (the principle of re-duce) which can save feed costs of Rp. 399,750, - / month and utilization of solid waste for organic fertilizer which gives a profit of Rp. 58,700, - / harvest. The strategies for implementing cleaner production are: Socializing the concept and conducting training on the implementation of cleaner production, production management and marketing to support the implementation of cleaner production. Keywords: Intensive duck farming, Cleaner production, SWOT analysis.